I heart New York - Kelk, Lindsey (New York Harper, 2010)
After causing a scene at a wedding where she discovered her boyfriend was cheating on her, Angela Clarke flees to Manhattan, where she gets a city makeover, a job blogging for a fashion magazine, and begins dating two men
1
Keywords: Blogs -- Fiction; New York (N.Y.) -- Fiction; Chick lit